Improving E-Service Quality of Indonesian Toll Road Application with Entrepreneurship Insights - Setiawan, Mohamad Agus; Hartoyo, Hartoyo; Seminar, Kudang Boro; Sartono, Bagus; Fitriati, Rachma; Ginting, Victor (Pandawan, 2025)
Digital transformation in Indonesia toll road sector faces significant challenges related to information fragmentation among Toll Road Operators (BUJT), hindering the optimization of electronic service quality (E-Service Quality). This research aims to enhance E-Service Quality through the Soft Systems Methodology (SSM), integrated with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis to understand key service dimensions. The findings indicate that integrating information across BUJTs, with a focus on informativeness, is critical to improving user satisfaction. The SSM-based conceptual model developed provides systemic solutions through policy integration, collaboration among BUJTs, and the development of an integrated information system. The assessment reveals that the proposed changes support toll road digital transformation and are culturally feasible. This study offers a strategic framework for improving toll road service quality, strengthening stakeholder collaboration, and creating a better user experience.